2017
DOI: 10.1038/srep40464
|View full text |Cite|
|
Sign up to set email alerts
|

Integrin β4 promotes cell invasion and epithelial-mesenchymal transition through the modulation of Slug expression in hepatocellular carcinoma

Abstract: Integrin β4 (ITGB4) is a transmembrane receptor involved in tumorigenesis and the invasiveness of many cancers. However, its role in hepatocellular carcinoma (HCC), one of the most prevalent human cancers worldwide, remains unclear. Here, we examined the involvement of ITGB4 in HCC and explored the underlying mechanisms. Real-time PCR and immunohistochemical analyses of tissues from 82 patients with HCC and four HCC cell lines showed higher ITGB4 levels in tumor than in adjacent non-tumor tissues and in HCC th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 53 publications
6
55
0
1
Order By: Relevance
“…Phosphoinositide 3-kinase (PI3K) and RhoA small gtpase were activated by integrin alpha 6 beta 4 bound to laminin. In addition, the interaction between integrin alpha6 beta4 and growth factor receptors included activation signaling pathways of the epidermal growth factor receptor family, such as PI3K AKT, and MAPK signaling was involved in tumorigenesis and metastasis [44]. Therefore, similar to our hypothesis, ITGB4 was associated with bone metastasis of bladder cancer and could be used as a prognostic marker in bladder cancer.…”
Section: Discussionsupporting
confidence: 68%
“…Phosphoinositide 3-kinase (PI3K) and RhoA small gtpase were activated by integrin alpha 6 beta 4 bound to laminin. In addition, the interaction between integrin alpha6 beta4 and growth factor receptors included activation signaling pathways of the epidermal growth factor receptor family, such as PI3K AKT, and MAPK signaling was involved in tumorigenesis and metastasis [44]. Therefore, similar to our hypothesis, ITGB4 was associated with bone metastasis of bladder cancer and could be used as a prognostic marker in bladder cancer.…”
Section: Discussionsupporting
confidence: 68%
“…On the basis of the associations between CUL7 expression and invasion depth, lymph node involvement and advanced clinical stage, CUL7 may promote EMT in EC cells. SNAI2 is a transcription factor that has been reported to be upregulated in various types of tumors and is associated with decreased expression of the epithelial marker E-cadherin and increased expression of the mesenchymal marker Vimentin, and may thus serve important roles in the regulation of EMT (18). In the present study, results from IHC and cell culture experiments suggested that CUL7 may enhance the expression levels of SNAI2 and Vimentin, and inhibit E-cadherin expression, and increase cell migration.…”
Section: Discussionsupporting
confidence: 49%
“…Manuscript to be reviewed migration, epithelial-mesenchymal transition, invasion, and metastasis in different cancers (Gan et al 2018;Huang et al 2017;Kitajiri et al 2002;Li et al 2017). The aberrant expression of ITGA11, ITGB4, and ITGB8 have been reported in many cancers (Grossman et al 2000;Mertens-Walker et al 2015;Parajuli et al 2017;Tagliabue et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, higher ITGB4 expression level was detected in tumor than adjacent non-tumor tissues in patients with hepatocellular carcinoma (HCC). Silencing of ITGB4 could repress cell proliferation, colony forming ability and cell invasiveness (Li et al 2017). Integrin β8, paired with αv subunit, is encoded by ITGB8.…”
Section: Introductionmentioning
confidence: 99%